2006
DOI: 10.2310/6650.2006.05018
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Reaction and Cytoskeletal Alterations in Endothelial Cells after Shock Wave Exposure

Abstract: SWC lesions were associated with a switch to an endothelial proinflammatory phenotype, with an impaired regeneration rate and changes in cytoskeletal functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although some recent literature suggests the use of a water bath to apply shock waves to cell cultured in flasks, we applied ESWs directly to cell suspension containing tubes to avoid the nonhomogeneous effects resulting from treatment of monolayer cells in flasks. In fact, it is reported that when treating cells in flasks, there are signs of significant cell detachment and injury close to the focus region . ESW dosage is higher at the center of the culture where cells may be damaged and eventually undergo apoptosis; on the contrary, cells at the edges receiving a lower dose are positively stimulated to proliferation and differentiation …”
Section: Discussionmentioning
confidence: 99%
“…Although some recent literature suggests the use of a water bath to apply shock waves to cell cultured in flasks, we applied ESWs directly to cell suspension containing tubes to avoid the nonhomogeneous effects resulting from treatment of monolayer cells in flasks. In fact, it is reported that when treating cells in flasks, there are signs of significant cell detachment and injury close to the focus region . ESW dosage is higher at the center of the culture where cells may be damaged and eventually undergo apoptosis; on the contrary, cells at the edges receiving a lower dose are positively stimulated to proliferation and differentiation …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, on day 5 the measured wound area of the ESWT-treated group was still larger than the respective one of the untreated group. One possible explanation of this phenomenon is that this initially delayed wound closure could be due to an additional tissue injury caused by the highly energetic shock waves, as observed in bones [17] and endothelial cells [18, 19]. Petechial bleeding observed immediately after the shock-wave treatment lends some support to this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…One of the better-characterised systems is flyer-plate model, shown in Fig. 4.7 [34]. In this experimental setup a Nd-Yt-Al--garnet (Nd-YAG) laser is used to generate a pulse directed toward a fused silica window coated with a thick layer of copper.…”
Section: Laser-based Systemsmentioning
confidence: 99%
“…Cells are cultured directly in the chamber, which can be placed on an inverted microscope to enable imaging using, for example, Fig. 4.7 The flyer-plate model for application of shock waves to cell cultures with or without surface cavitation (Adapted from Sondén et al [34]). A Laser Pulse, generated with a Nd-YAG (neodymium:yttrium-aluminium-garnet) pulsed laser and monitored by an energy Meter, is reflected with a Mirror and focused with a Lens towards a Perforated Stand at the base of the sample stage.…”
Section: Mechanical Deformation Systemsmentioning
confidence: 99%